Preparation method of anti-scaling cathode with micro-nano layered structure
By preparing anti-scaling electrodes with micro-nano-layered structure on the cathode, using the combination of anodizing, electrodeposition and inert protective shells, the automatic falloff of scale crystals is achieved, solving the cathode scaling problem and improving electrochemistry Reaction stability and equipment life.
Patent Information
- Application Number
- CN202411323016.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The prior art is difficult to effectively prevent cathode scaling, resulting in accumulation of scale crystals on the cathode surface during the electrochemical reaction, affecting reaction efficiency and equipment life.
Using the anti-scatter cathode preparation method with a micro-nano layered structure, it can be formed automatically by anodizing of the metal microarray structure, electrodeposition of the micro-nano layered structure, activation of the alkali-resistant protective layer and thermal curing of the inert protective shell. Electrode that removes the dirt crystal.
It realizes the automatic falloff of scale crystals, extends the service life of the electrode, improves the stability and efficiency of electrochemical reactions, and effectively solves the cathode scaling problem.
Smart Images

Figure CN119194484A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrodes and relates to a method for preparing an anti-scaling cathode with a micro-nano layered structure. Background Art
[0002] Electrochemical technology has shown great potential in the field of green energy and environmental protection, and is highly consistent with the "dual carbon" goal. This technology can use green energy to produce hydrogen from seawater, extract lithium from salt lakes, and desalinate brackish water without adding chemical agents, reflecting its environmental protection and high efficiency. However, one of the key technical difficulties faced in the application of this technology is cathode scaling. The reason for cathode scaling is that the electrolysis reaction of water causes OH near the cathode surface to - The concentration increases with HCO 3- , Ca 2+ Mg 2+ The reaction produces insulating CaCO3 and Mg(OH)2, which precipitate on the cathode surface and gradually accumulate to form a hard deposit layer. Since calcium and magnesium ions exist in most real water, such as natural seawater, which contains a large amount of calcium ions (0.4268g / L) and magnesium ions (1.3307g / L), as long as the cathode decomposes water (2H2O+e - →2OH - +H2↑) reaction, there will be scale crystals precipitated on the cathode surface, which makes cathode scaling in the electrochemical reaction process in actual water inevitable. Therefore, the inherent scaling phenomenon is plaguing the application of electrochemical technology in actual water.
[0003] At present, there are few reports on preventing cathode scaling at home and abroad. The reference paper Direct seawater electrolysis by adjusting the local reaction environment of a catalyst reports the introduction of a Lewis acid layer on the cathode surface to capture OH - Preventing the solution pH from rising prevents the formation of scale crystals in the solution. -The capture on the surface exacerbates the nucleation of scale crystals on the electrode surface. In addition, the phase change membrane reported in the reference Amembrane-based seawater electrolyser for hydrogen generation converts seawater into pure water for electrolysis in situ through the mechanism of phase change migration. However, the wetting problem of the hydrophobic phase change membrane seriously restricts the development of this method. In addition, the reference Efficient bubble / precipitate trafficable stable seawater reduction electrocatalysis at conventional-level current densities constructs a honeycomb 3D cathode to produce a large number of small-sized H2 bubbles to achieve uninterrupted exclusion of Mg 2+ and Ca 2+ However, this method uses natural wood to make electrodes, which is difficult to apply on a large scale because natural wood is easy to break during the carbonization process. In addition, the reference Visualization of crystal automatic exfoliation on an anti-scaling cathode with well-ordered hydrophobic microcones discovered the mechanism of automatic shedding of scale crystals using copper nanotips highly dispersed on an inert surface. However, the easy alkali corrosion of copper causes the nanotips to fall off after 8 hours of use, thereby losing the anti-scaling function, so this electrode lacks practical application value.
[0004] The above methods have made some contributions to the research on cathode anti-scaling, but still have not solved this problem. Obviously, to completely solve this problem, it is necessary to develop a new cathode that can realize the automatic shedding function of scale crystals. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an anti-scaling cathode with a micro-nano layered structure.
[0006] The technical solution of the present invention:
[0007] A method for preparing an anti-scaling cathode with a micro-nano layered structure, the steps are as follows:
[0008] (1) Preparation of metal microarray structure: Prepare a Cl - and OH - The mixed solution is used as the electrolyte, the metal wire bundle is fixed in the electrolyte, anodized for 1-300 minutes under constant temperature and constant voltage conditions of 1-99°C, and then rinsed for standby use;
[0009] (2) Preparation of micro-nano hierarchical structure: A solution of nickel salt, iron salt, cobalt salt, crystal surface protectant, buffer and surfactant is used as the electrolyte, and a constant current density of 1-200 mA / cm is used under a constant temperature of 1-99 °C. 2 The reaction lasts for 1-300 minutes, and a nanostructure is prepared on the microarray structure to obtain a material with a micro-nano hierarchical structure;
[0010] (3) Construction of alkali-resistant protective layer: The material with micro-nano layered structure is placed under a constant temperature of 1-99°C with OH - A solution with a concentration of 0.05-20 mol / L is used as an electrolyte, and after being activated by repeated cyclic voltammetry scanning for 1-50,000 times in a potential range of 1-20 V vs RHE, a micro-nano hierarchical structure material resistant to alkali corrosion is obtained;
[0011] (4) Preparation of an inert protective shell: The alkali-resistant micro-nano layered structure material is placed vertically in a mold, a release agent is added, and then an inert slurry mixed with an inert reagent, a curing agent and a binder is poured into the mold, and thermally cured at 50-450°C for 1-300 min under an inert atmosphere to finally obtain a micro-nano layered anti-scaling electrode.
[0012] In step (1), Cl - and OH - The mass ratio is 2-40:1-30.
[0013] In step (1), the material of the metal wire bundle includes but is not limited to stainless steel, iron, copper, titanium, nickel, silver, platinum, etc.
[0014] In step (1), the metal wire bundle is placed vertically, and the length of the metal wire bundle immersed in the electrolyte accounts for 0.1%-20% of the total length. If the length of the metal wire bundle immersed is too short, the part below the liquid surface will not fall off due to gravity, while if the length is too long, the current density at the liquid surface will be too low to etch the metal wire.
[0015] In step (1), the relationship between the voltage of anodization and the cross-sectional area of the metal wire bundle is 0.1-50V / cm 2 If the voltage is too low, the metal wire cannot be etched, and if the voltage is too high, the metal wire will be over-etched and lose its microstructure.
[0016] In step (2), the mass ratio of nickel salt, iron salt, cobalt salt, crystal surface protecting agent, buffer and surfactant is 1-40:0.1-15:0.1-15:1-20:0.01-10:0.005-5.
[0017] In step (2), nickel salts include but are not limited to nickel chloride, nickel sulfate, nickel nitrate, nickel sulfamate, etc. Iron salts include but are not limited to ferrous chloride, ferrous sulfate, ferrous nitrate, etc. Cobalt salts include but are not limited to cobalt chloride, cobalt sulfate, cobalt nitrate, cobalt carbonate, etc. Crystal surface protective agents include but are not limited to sodium chloride, calcium chloride, ammonium chloride, sodium citrate, sodium dihydrogen phosphate, etc. Buffers include but are not limited to boric acid, potassium hydroxide, etc. Surfactants include but are not limited to sodium dodecyl sulfate, sodium dodecyl sulfonate, etc.
[0018] In step (2), the size of the microarray structure is greater than 2 μm, and the morphology includes but is not limited to cone, column, flower, needle, sphere, etc. The size of the nanostructure is less than 800 nm, and the morphology includes but is not limited to cone, column, flower, needle, sphere, etc.
[0019] In step (4), the volume ratio of the release agent to the volume of the mold used for casting is 1%-15%. The volume of the release agent determines the exposure degree of the micro-nano hierarchical structure. If the volume of the release agent is too low, the micro-nano hierarchical structure will be covered by the inert protective shell, while if the volume of the release agent is too high, the distance between the micro-nano hierarchical structure and the inert surface will be too large, which will not only increase the size of the crystal nucleation site, but also weaken the protective effect of the bubble layer.
[0020] In step (4), the mass ratio of the inert reagent, the curing agent and the binder is 1-79:1-12:20-89.
[0021] In step (4), the inert reagent includes but is not limited to polytetrafluoroethylene, dodecanethiol, perfluorodecyltrimethoxysilane, etc. The binder includes but is not limited to epoxy resin, polydimethylsiloxane, acrylic resin, etc. The curing agent includes but is not limited to vinyl-terminated polydimethylsiloxane, organic anhydride, imidazoles, modified amines, etc.
[0022] Beneficial effects of the present invention: The anti-scaling cathode with a micro-nano layered structure of the present invention realizes that the active sites are dispersed on the inert surface. This structure can utilize the generated H2 microbubbles to migrate along the inert surface and aggregate into a bubble layer, thereby preventing the cathode surface from contacting H2O, Ca 2+ 、HCO3 -contact. This causes the scale crystals to grow only in chains on the smaller active sites. Subsequently, the vibrations generated by the H2 bubbles growing larger and bursting cause the scale crystal chains standing on the active sites to automatically fall off. This process is repeated to achieve a dynamic equilibrium process in which the scale crystals automatically fall off. In addition, the micro-nano hierarchical structure can not only further reduce the size of the scale crystal nucleation sites, but also increase the density and dispersion of the active sites. And through self-activation, the surface of the micro-cone array has the function of alkali corrosion resistance, which effectively solves the problem of short life of the active sites of the micro-cone array. At the same time, the cast inert shell has high mechanical strength and chemical stability, which effectively solves the problem of short life of the inert surface. In summary, the present invention is expected to fundamentally solve the problem of cathode scaling and further promote the development of electrochemical technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a preparation flow chart of the present invention.
[0024] Figure 2 This is a partial SEM image of the microarray structure.
[0025] Figure 3 This is a scanning electron microscope image of the micro-nano layered structure.
[0026] Figure 4 This is a physical picture of the anti-scaling electrode with a micro-nano layered structure.
[0027] Figure 5 This is a scanning electron microscope image of the material without microarray structure.
[0028] Figure 6 This is a scanning electron microscope image of a material without nanostructures.
[0029] Figure 7 It is the mass increment and homogeneous nucleation rate diagram of the anti-scaling electrode during 154h operation. DETAILED DESCRIPTION
[0030] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0031] Example 1
[0032] A method for preparing an anti-scaling electrode with a micro-nano layered structure is as follows:
[0033] (1) Nickel wire was used as the substrate. A mixed solution of sodium chloride and potassium hydroxide with a mass ratio of 2:30 was prepared as the electrolyte. 2 20% of one end of the nickel wire bundle was immersed in the electrolyte and anodized for 5 minutes at a constant temperature of 45°C and a constant voltage of 25V, and then rinsed with water for later use. Figure 2 shown.
[0034] (2) Electrodeposition was carried out in a two-electrode electrochemical system. The mass ratio of nickel sulfate, ferrous sulfate, cobalt sulfate, ammonium chloride, boric acid and sodium dodecyl sulfate in the electrodeposition solution was 8:3:3:2:4.5:0.005. The electrodeposition temperature was 35°C and the current density was 5 mA / cm 2 Electrodeposition was performed for 300 minutes. After deposition, the sample was removed from the electrolyte, thoroughly rinsed with water and ethanol, and stored in anhydrous ethanol. Figure 3 shown.
[0035] (3) The electrodeposited material was subjected to 50,000 repetitive cyclic voltammetry scan activation at 45° C. in a potential range of 19-20 V vs RHE using a 0.05 mol / L sodium hydroxide aqueous solution as an electrolyte, and then cleaned with water for later use.
[0036] (4) The micro-nano layered metal material was placed vertically in a mold with a volume of 8 mL, and then 0.08 mL of a release agent was added. Then, an inert slurry mixed with polytetrafluoroethylene, vinyl-terminated polydimethylsiloxane and polydimethylsiloxane in a mass ratio of 55:5:40 was poured into the mold, and thermally cured at 160°C for 120 min under an argon atmosphere to finally obtain a micro-nano layered anti-scaling electrode. The prepared anti-scaling electrode is shown in Figure 4 .
[0037] Example 2
[0038] (1) Stainless steel wire is used as the substrate. A mixed solution of potassium chloride and sodium hydroxide with a mass ratio of 40:1 is prepared as the electrolyte. 2 0.1% of one end of the stainless steel wire bundle was immersed in the electrolyte, anodized for 300 min at a constant temperature of 35°C and a constant voltage of 10 V, and then rinsed with water for standby use.
[0039] (2) Electrodeposition was carried out in a two-electrode electrochemical system. The mass ratio of nickel chloride, ferrous chloride, cobalt chloride, sodium citrate, boric acid and sodium dodecyl sulfate in the electrodeposition solution was 40:0.1:15:20:10:5. The electrodeposition temperature was 85°C and the current density was 150 mA / cm 2 The electrodeposition was performed for 3 minutes. After deposition, the sample was removed from the electrolyte, rinsed thoroughly with water and ethanol, and stored in anhydrous ethanol.
[0040] (3) The electrodeposited material was subjected to 20 repeated cyclic voltammetric scan activation at 75° C. in a potential range of 1-5 V vs RHE using a 20 mol / L potassium hydroxide aqueous solution as an electrolyte, and then cleaned with water for later use.
[0041] (4) The micro-nano layered metal material was placed vertically in a mold with a volume of 720 mL, and then 108 mL of a release agent was added. Then, an inert slurry mixed with dodecanethiol, modified amine and epoxy resin in a mass ratio of 1:12:87 was poured into the mold, and thermally cured at 50°C for 10 min under a nitrogen atmosphere to finally obtain a micro-nano layered anti-scaling electrode.
[0042] Example 3
[0043] (1) Titanium wire was used as the substrate. A mixed solution of sodium chloride and potassium hydroxide with a mass ratio of 2:30 was prepared as the electrolyte. 2 10% of one end of the titanium wire bundle was immersed in the electrolyte, anodized for 1 min at a constant temperature of 1°C and a constant voltage of 25 V, and then rinsed with water for standby use.
[0044] (2) Electrodeposition was carried out in a two-electrode electrochemical system. The mass ratio of nickel nitrate, ferrous nitrate, cobalt nitrate, sodium chloride, potassium hydroxide and sodium dodecyl sulfate in the electrodeposition solution was 15:15:0.1:20:0.01:5. The electrodeposition temperature was 99°C and the current density was 200 mA / cm 2 Electrodeposition was performed for 1 minute. After deposition, the sample was removed from the electrolyte, rinsed thoroughly with water and ethanol, and stored in anhydrous ethanol.
[0045] (3) The electrodeposited material was subjected to 50 repeated cyclic voltammetric scan activation at 99° C. in a potential range of 2-5 V vs RHE using a 0.1 mol / L sodium hydroxide aqueous solution as an electrolyte, and then cleaned with water for later use.
[0046] (4) The micro-nano layered metal material was placed vertically in a mold with a volume of 8 mL, and then 0.4 mL of a release agent was added. Then, an inert slurry mixed with polytetrafluoroethylene, vinyl-terminated polydimethylsiloxane and polydimethylsiloxane in a mass ratio of 79:1:20 was poured into the mold, and thermally cured at 450°C for 30 min under an argon atmosphere to finally obtain a micro-nano layered anti-scaling electrode.
[0047] Example 4
[0048] (1) Silver wire was used as the substrate. All solutions in the experiment were prepared with analytical grade chemicals and ultrapure water. A mixed solution of potassium chloride and sodium hydroxide with a mass ratio of 10:5 was prepared as the electrolyte. 2 0.1% of one end of the silver wire bundle was immersed in the electrolyte, anodized for 3 minutes at a constant temperature of 99°C and a constant voltage of 5V, and then rinsed with water for standby use.
[0049] (2) Electrodeposition was carried out in a two-electrode electrochemical system. The mass ratio of nickel sulfamate, ferrous chloride, cobalt carbonate, sodium dihydrogen phosphate, boric acid and sodium dodecyl sulfate in the electrodeposition solution was 1:15:15:1:10:0.5. The electrodeposition temperature was 75°C and the current density was 1 mA / cm 2 The electrodeposition was carried out for 300 minutes. After deposition, the sample was removed from the electrolyte, rinsed thoroughly with water and ethanol, and stored in anhydrous ethanol.
[0050] (3) The electrodeposited material was subjected to repeated cyclic voltammetry scanning activation at 75° C. in a potential range of 5-15 V vs RHE using a 20 mol / L potassium hydroxide aqueous solution as an electrolyte, and then cleaned with water for later use.
[0051] (4) The micro-nano layered metal material was placed vertically in a mold with a volume of 180 mL, and then 9 mL of a release agent was added. Then, an inert slurry mixed with dodecanethiol, modified amine and epoxy resin in a mass ratio of 2:9:89 was poured into the mold, and thermally cured at 150 °C for 1 min under a nitrogen atmosphere to finally obtain a micro-nano layered anti-scaling electrode.
[0052] Comparative Example 1
[0053] The constant voltage in step (1) of Example 1 was changed to 55 V. The scanning electron microscope image of the obtained material microstructure is as follows: Figure 5 As shown in Figure 2, due to the excessive anodization voltage, the metal wire bundles were over-etched and the microarray structure could not be formed.
[0054] Comparative Example 2
[0055] The current density in step (2) of Example 1 was changed to 300 mA / cm 2 The scanning electron microscope image of the material microstructure is shown in Figure 6 As shown in Figure 2, the electrodeposition current density is too large, so the electrodeposition cannot form nanostructures.
[0056] Comparative Example 3
[0057] The amount of the release agent in step (4) of Example 1 was changed to 0.05 mL. Since too little release agent was added, the metal part was completely covered by the inert protective shell, causing the material to lose its conductivity.
[0058] Comparative Example 4
[0059] The constant voltage in step (1) of Example 1 was changed to 0.05 V. Since the anodization voltage was too low, the metal wire bundle could not be etched and the microarray structure could not be formed.
[0060] Comparative Example 5
[0061] The current density in step (2) of Example 1 was changed to 0.5 mA / cm 2 Since the electrodeposition current density is too small, the electrodeposition cannot form nanostructures.
[0062] Comparative Example 6
[0063] The volume of the release agent in step (4) of Example 1 was changed to 2 mL. Since too much release agent was added, the metal wire was exposed too much and could not be protected by the inert protective layer, so it did not have the anti-fouling performance.
[0064] Comparative Example 7
[0065] The heat curing temperature in step (4) of Example 2 was changed to 460° C. Since the heat treatment temperature was too high, the inert protective shell was carbonized and lost its inert effect.
[0066] Comparative Example 8
[0067] The heat curing temperature in step (4) of Example 2 was changed to 30° C. Since the heat treatment temperature was too low, the inert protective shell could not be cured and thus could not be formed.
[0068] Comparative Example 9
[0069] The length of the metal wire bundle immersed in the electrolyte in step (1) of Example 3 is changed to 25%. Since too much of the metal wire bundle is immersed in the electrolyte, the current density at the liquid surface is too low to etch the metal wire.
[0070] Comparative Example 10
[0071] The length of the metal wire bundle immersed in the electrolyte in step (1) of Example 3 was changed to 0.05%. Since too little of the metal wire bundle was immersed in the electrolyte, the metal wire portion below the liquid surface would not fall off due to gravity, and thus a microarray structure could not be formed.
[0072] The long-term anti-scaling experiment of the electrode was carried out in an electrochemical reaction tank. The anode and cathode used RuO2-IrO2-TiO2 / Ti mesh and the anti-scaling electrode obtained in Example 1, respectively. 2+ A solution with a concentration of 1 g / L was used as the electrolyte. During the reaction, a DC power supply was applied at 100 mA / cm 2 The constant current density was run for 154 hours. The experimental results are shown in Figure 7 As shown, the anti-scaling rate of the anti-scaling electrode of the present invention is stably maintained at more than 99% during the long-term operation of 154 hours, indicating that the present invention not only has an excellent anti-scaling effect but also has the advantage of a long life.
Claims
1. A method for preparing an anti-scaling cathode having a micro-nano layered structure, characterized in that: Here are the steps: (1) Preparation of metal microarray structure: Prepare a Cl - and OH - The mixed solution is used as the electrolyte, the metal wire bundle is fixed in the electrolyte, anodized for 1-300 minutes under constant temperature and constant voltage conditions of 1-99°C, and then rinsed for standby use; (2) Preparation of micro-nano hierarchical structure: A solution of nickel salt, iron salt, cobalt salt, crystal surface protectant, buffer and surfactant is used as the electrolyte, and a constant current density of 1-200 mA / cm is used under a constant temperature of 1-99 °C. 2 The reaction lasts for 1-300 min, and a nanostructure is prepared on the microarray structure to obtain a material with a micro-nano hierarchical structure; (3) Construction of alkali-resistant protective layer: The material with micro-nano layered structure is placed under a constant temperature of 1-99°C with OH - A solution with a concentration of 0.05-20 mol / L is used as an electrolyte, and after being activated by repeated cyclic voltammetry scanning for 1-50,000 times in a potential range of 1-20 V vs RHE, a micro-nano hierarchical structure material resistant to alkali corrosion is obtained; (4) Preparation of an inert protective shell: The alkali-resistant micro-nano layered structure material is placed vertically in a mold, a release agent is added, and then an inert slurry mixed with an inert reagent, a curing agent and a binder is poured into the mold, and thermally cured at 50-450°C for 1-300 min under an inert atmosphere to finally obtain a micro-nano layered anti-scaling electrode.
2. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (1), Cl - and OH - The mass ratio is 2-40:1-30.
3. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (1), the material of the metal wire bundle is stainless steel, iron, copper, titanium, nickel, silver, or platinum. The metal wire bundle is placed vertically, and the length of the metal wire bundle immersed in the electrolyte accounts for 0.1%-20% of the total length.
4. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (1), the relationship between the voltage of anodization and the cross-sectional area of the metal wire bundle is 0.1-50V / cm 2 .
5. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (2), the mass ratio of nickel salt, iron salt, cobalt salt, crystal surface protecting agent, buffer and surfactant is 1-40:0.1-15:0.1-15:1-20:0.01-10:0.005-5.
6. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (2), the nickel salts include nickel chloride, nickel sulfate, nickel nitrate, and nickel sulfamate; the iron salts include ferrous chloride, ferrous sulfate, and ferrous nitrate; the cobalt salts include cobalt chloride, cobalt sulfate, cobalt nitrate, and cobalt carbonate; the crystal surface protective agents include sodium chloride, calcium chloride, ammonium chloride, sodium citrate, and sodium dihydrogen phosphate; the buffers include boric acid and potassium hydroxide; and the surfactants include sodium dodecyl sulfate and sodium dodecyl sulfonate.
7. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (2), the size of the microarray structure is greater than 2 μm, and the morphology is cone, column, flower, needle, or sphere; the size of the nanostructure is less than 800 nm, and the morphology is cone, column, flower, needle, or sphere.
8. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (4), the volume ratio of the release agent to the volume of the mold used for casting is 1%-15%.
9. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (4), the mass ratio of the inert reagent, the curing agent and the binder is 1-79:1-12:20-89.
10. The method for preparing an anti-scaling cathode having a micro-nano layered structure according to claim 1, characterized in that: In step (4), the inert reagent is polytetrafluoroethylene, dodecanethiol, perfluorodecyltrimethoxysilane; the binder is epoxy resin, polydimethylsiloxane, acrylic resin; and the curing agent is vinyl-terminated polydimethylsiloxane, organic acid anhydride, imidazoles, and modified amines.
Citation Information
Patent Citations
Method for preparing self-supporting three-dimensional bifunctional catalytic electrode with porous structure
CN110205636A
Preparation method of anti-scaling electrode capable of automatically falling off incrustation scale
CN117142579A
Cited By
Self-cleaning electrochemical descaling cathode material and preparation method and application thereof
CN121292589A
